TINJAUAN YURIDIS SENGKETA HAK WARIS TANAH YANG DIKUASAI SECARA MELAWAN HUKUM (STUDI PUTUSAN NO.09/PDT.G/2013/PN.BINJAI) - wagirin wagirin wagirin (Ilmu Hukum Prima (IHP), 2018)
Research on inheritance rights disputes is an important topic to discuss because issues related to inheritance often occur in the community. This thesis discusses the dispute over inheritance rights of land that is controlled by the law. The objective of writing the thesis is to find out the inheritance system in the Civil Code, the provisions of inheritance rights on land and the judicial legal review in the decision Number: 09 / PDT.G / 2013 / PN. Binjai. Based on the scope and problem in this study, the research was used a normative juridical research method. This normative juridical approach is used to analyze written law from library materials and reference material in the field of law or based on the Civil Code and other relevant laws and regulations, so that the description of the answers to the problem can be known. The results of this study revealed that inheritance law is a law that regulates the transfer of assets left by someone who died and its consequences for his heirs, and registration of transfer of rights because inheritance is needed in order to provide legal protection to the heirs so that the inheritance rights dispute can be avoided especially disputes are committed against law. An illegal act will only cause a loss. A loss caused by an illegal act must pay compensation because the action caused a loss caused by an act of action against the law by the perpetrator.